An anchored chromosome‐scale genome assembly of spinach improves annotation and reveals extensive gene rearrangements in euasterids. Issue 2 (10th June 2021) - Hulse‐Kemp, Amanda M; Bostan, Hamed; Chen, Shiyu; Ashrafi, Hamid; Stoffel, Kevin; Sanseverino, Walter; Li, Linzhou; Cheng, Shifeng; Schatz, Michael C.; Garvin, Tyler; du Toit, Lindsey J.; Tseng, Elizabeth; et al.
Abstract: Spinach ( Spinacia oleracea L.) is a member of the Caryophyllales family, a basal eudicot asterid that consists of sugar beet ( Beta vulgaris L. subsp. vulgaris ), quinoa ( Chenopodium quinoa Willd.), and amaranth ( Amaranthus hypochondriacus L.). With the introduction of baby leaf types, spinach has become a staple food in many homes. Production issues focus on yield, nitrogen‐use efficiency and resistance to downy mildew ( Peronospora effusa ). Although genomes are available for the above species, a chromosome‐level assembly exists only for quinoa, allowing for proper annotation and structural analyses to enhance crop improvement. We independently assembled and annotated genomes of the cultivar Viroflay using short‐read strategy (Illumina) and long‐read strategies (Pacific Biosciences) to develop a chromosome‐level, genetically anchored assembly for spinach. Scaffold N50 for the Illumina assembly was 389 kb, whereas that for Pacific BioSciences was 4.43 Mb, representing 911 Mb (93% of the genome) in 221 scaffolds, 80% of which are anchored and oriented on a sequence‐based genetic map, also described within this work. The two assemblies were 99.5% collinear. Independent annotation of the two assemblies with the same comprehensive transcriptome dataset show that the quality of the assembly directly affects the annotation with significantly more genes predicted (26, 862 vs. 34, 877) in the long‐read assembly. Analysis of resistance genes confirms a bias in resistant gene motifs more typical of monocots. Evolutionary analysis indicates that Spinacia is a paleohexaploid with a whole‐genome triplication followed by extensive gene rearrangements identified in this work. Diversity analysis of 75 lines indicate that variation in genes is ample for hypothesis‐driven, genomic‐assisted breeding enabled by this work. Core Ideas: Quality of genome assemblies directly affect quality of annotation. Analysis of resistance genes confirms a bias in resistant gene motifs more typical of monocots. Spinacia is a paleohexaploid with extensive gene rearrangements. Variation in genes is ample for hypothesis‐driven genomic‐assisted breeding.